Pengaruh Penggunaan Model Pembelajaran Example Non Example Terhadap Hasil Belajar Siswa Materi Tata Cara Shalat pada Siswa Kelas IV SDN 20 Jongkat Tahun Ajaran 2025/2026 - Apriana, Diana; Eli; Imran, Yusida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using the Example Non Example learning model on the learning outcomes of fourth-grade students at SDN 20 Jongkat regarding the procedures for performing prayer during the 2025/2026 academic year. The issues examined in this study are: 1) What were the students' learning outcomes regarding the procedures of prayer prior to the implementation of the Example Non Example learning model in Grade IV at SDN 20 Jongkat?, 2). How well can Grade IV students at SDN 20 Jongkat learn the procedures of prayer following the implementation of the Example Non Example learning model?, 3). Is there an effect of the Example Non Example learning model on learning outcomes regarding the procedures of prayer for fourth grade students at SDN 20 Jongkat?. The research method employed is an experimental method specifically a quasi experimental design using a quantitative approach. The population in this study was class IV, and sample used consisted of class IV A as the experimental group and class IV B as the control group. The data analysis techniques employed include descriptive statistics, homogeneity testing, normality testing, and hypothesis testing using a non-parametric test specifically, the Wilcoxon test. The results of this study indicate that the use of the Example Non Example instructional medium has a significant influence on improving students' learning outcomes regarding the procedures for performing prayer. The research results indicate an effect of using the Example Non Example learning medium on student learning outcomes, based on the Wilcoxon Signed-Rank Test, a Z-value of -2.352 was obtained, with an Asymp. Sig. (2-tailed) value of 0.019 for the experimental class. Since this value is smaller than the significance level of 0.05 (0.019 < 0.05), there is a significant difference in learning outcomes before and after the use of the Example Non Example learning medium.